Conductive belt, image forming apparatus having the same, and method for manufacturing the conductive belt

A conductive belt with a polyethylene and polyamide substrate, epoxy adhesive, and acid-modified ethylene-tetrafluoroethylene surface layer addresses transport complexity and solvent resistance, ensuring reliable and cost-effective paper conveyance in image forming devices.

JP7627634B2Active Publication Date: 2025-02-06OKURA INDUSTRIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021130385
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-07
Publication Date
2025-02-06
Estimated Expiration
2041-08-07

AI Technical Summary

Technical Problem

Conventional image forming devices face issues with paper transport using belts, such as complex structures due to vacuum suction methods and electrostatic attraction methods that require complicated manufacturing processes, solvent resistance problems with inkjet inks, and warping due to moisture absorption in multi-layer conductive belts.

Method used

A conductive belt composed of a substrate layer containing polyethylene resin, polyamide resin, and a conductive agent, with an adhesive layer of epoxy group-containing polyethylene resin, and a surface layer of acid-modified ethylene-tetrafluoroethylene copolymer, manufactured via coextrusion, ensuring uniform resistivity and resistance to warping.

Benefits of technology

The conductive belt provides reliable paper conveyance with strong adsorption force, resistance to solvent swelling, and maintains shape under high humidity, while being cost-effective and suitable for high-speed inkjet printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627634000001
    Figure 0007627634000001
Patent Text Reader

Abstract

To provide a belt for an image forming device in which a base material layer exhibits semi-conductivity in a medium resistance region (1×105 to 1×108 Ω / sq), a variation in surface resistivity is small, and a surface layer exhibits insulating properties.SOLUTION: A conductive belt includes: a base material layer made of a composition containing polyethylene resin, polyamide resin and conductive agent; an adhesive layer made of a composition containing epoxy group-containing polyethylene resin; and a surface layer made of a composition containing acid-modified ethylene-tetrafluoroethylene copolymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive belt for use in an image forming apparatus using an inkjet system or an electrophotographic system. [Background technology]

[0002] Conventionally, image forming devices such as electrophotographic and inkjet printers, copiers, and facsimiles have used rollers to transport paper, but as image formation speeds increase, problems tend to occur with rollers when transporting paper, so methods are being adopted in which a belt reliably supports and transports paper.Specifically, known methods include (1) a method in which a belt with suction holes is used to suck paper onto the belt by reducing pressure and suction, and (2) a method in which a belt made of a conductive base layer and an insulating surface layer is used, and a voltage is applied to the belt to generate electrostatic adsorption force to attract paper to the belt and transport it.

[0003] Of these, (1) the method of sucking the paper to the belt by reducing pressure requires a pressure reduction chamber and a pressure reduction device for reducing the pressure in the pressure reduction chamber as described in Patent Document 1 and Patent Document 2, and furthermore, the space between the driven belt and the pressure reduction chamber must be kept sealed at all times, which complicates the structure of the image forming apparatus. On the other hand, (2) the method of using electrostatic attraction is simple because the suction force can be controlled simply by adjusting the applied voltage if there is a member for applying voltage to the belt and a power source.

[0004] Patent Document 3 describes a belt (paper transport belt) that uses electrostatic attraction to attract and transport recording media such as paper, in which both the inner and outer layers are made of polyimide resin and the volume resistivity of the inner layer is 1×10 8 ~1×10 14 Ω cm, the volume resistivity of the outer layer is 1×10 14 ~1×10 16However, the paper transport belt described in Patent Document 3 requires centrifugal molding (a process is required in which a solution of polyamic acid for the inner or outer layer is sprayed onto the front or back of a mold, the solvent is evaporated at high temperature, and then imidization is performed at high temperature in the absence of oxygen. In the case of two layers, this process is repeated twice), making the manufacturing process very complicated.

[0005] In addition, Patent Document 4 describes a method in which the inner layer is made of a conductive polyimide resin and has a surface resistivity of 1×10 4 ~1×10 9 The paper transport belt for inkjet printing is described, with the outer layer being made of ethylene-tetrafluoroethylene copolymer (ETFE) and the inner layer being made of Ω / □. This paper transport belt also requires a process of forming the inner layer by centrifugal molding, covering it with a preformed tubular ETFE and melt-bonding it, so the manufacturing process is very complicated.

[0006] On the other hand, some inks used in inkjet printers capable of printing at high speeds contain organic solvents, and when the ink adheres to the belt, depending on the type of resin used in the belt, that part can swell, causing unevenness on the belt surface. In view of this solvent resistance, it is desirable to use fluororesin for the surface layer, but fluororesin has poor adhesion. In addition, some fluororesins have a surface resistivity of 1×10 14 Some have less than Ω / □, which can cause the problem of weak suction power. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-131389 A [Patent Document 2] JP 2019-127364 A [Patent Document 3] JP 2008-94605 A [Patent Document 4] JP 2011-73804 A Summary of the Invention [Problem to be solved by the invention]

[0008] In view of this situation, in order to manufacture a multi-layer conductive belt by co-extrusion, a polyamide resin containing a conductive agent and a surface resistivity of 1×10 5 ~1×10 8 A conductive belt was prototyped that had a base layer with a resistance of Ω / □ and a surface layer containing an acid-modified ethylene-tetrafluoroethylene copolymer, but a problem occurred in which the ends of the conductive belt warped when it absorbed moisture. The present invention has been made in consideration of such problems, and the base material layer is in the medium resistance region (1×10 5 ~1×10 8 The objective of the present invention is to provide a conductive belt that exhibits semiconductivity of 300 Ω / □, has small variations in surface resistivity, has an insulating surface layer, and does not warp when absorbing moisture. [Means for solving the problem]

[0009] According to the present invention, (1) A conductive belt comprising a substrate layer made of a composition containing a polyethylene resin, a polyamide resin, and a conductive agent, an adhesive layer made of a composition containing an epoxy group-containing polyethylene resin, and a surface layer made of a composition containing an acid-modified ethylene-tetrafluoroethylene copolymer; (2) The conductive belt according to (1), wherein the composition for forming the base layer further contains a compatibilizer; (3) The conductive belt according to (1) or (2), wherein the epoxy group-containing polyethylene resin is an ethylene-glycidyl methacrylate copolymer; (4) The conductive belt according to any one of (1) to (3), wherein the conductive agent is an electronic conductive material; (5) The conductive belt according to (4), wherein the electronic conductive material is carbon black; (6) The surface resistivity of the base layer side at a temperature of 23° C. and a relative humidity of 50% RH is 1×10 5 Ω / □ or more 1×108 The conductive belt according to any one of (1) to (5), characterized in that the resistance is Ω / □ or less; (7) The surface resistivity of the surface layer side at a temperature of 23° C. and a relative humidity of 50% RH is 1×10 13 The conductive belt according to any one of (1) to (6), characterized in that the resistivity is Ω / □ or more; (8) The conductive belt according to any one of (1) to (7) above, which is used in an image forming apparatus; (9) The conductive belt according to any one of (1) to (8) above, which is used in an inkjet type image forming apparatus; (10) An image forming apparatus comprising the conductive belt according to any one of (1) to (9); (11) A method for producing a conductive belt according to any one of (1) to (9), characterized in that a base layer-forming composition containing a polyethylene resin, a polyamide resin and a conductive agent, an adhesive layer-forming composition containing an epoxy group-containing polyethylene resin, and a surface layer-forming composition containing an acid-modified ethylene-tetrafluoroethylene copolymer are each fed into separate extruders, and co-extruded through a circular die so that the base layer is an inner layer, the adhesive layer is an intermediate layer, and the surface layer is an outer layer; is provided. Effect of the Invention

[0010] The conductive belt of the present invention is a laminate of a base layer made of a composition containing a polyethylene resin, a polyamide resin, and a conductive agent, an adhesive layer made of a composition containing an epoxy group-containing polyethylene resin, and a surface layer made of a composition containing an acid-modified ethylene-tetrafluoroethylene copolymer, and has a high interlayer peel strength and a surface resistivity of 1×10 on the surface layer side. 13 Ω / □ or more (insulating region), and the surface resistivity of the base layer side (the side on which the surface layer is not formed) is 1×10 5 ~1×10 8A conductive belt with a resistance in the range of Ω / □ (medium resistance region) can be obtained. When such a belt is used as a paper transport belt, the surface layer has excellent insulating properties, so the adhesive force of the recording medium (paper) is strong and the recording medium can be transported reliably. Furthermore, the conductive belt of the present invention is unlikely to warp even under high humidity conditions, and can be suitably used as a paper transport belt. The conductive belt of the present invention can be manufactured more cheaply than a conventional multi-layer belt using a polyimide resin. The conductive belt of the present invention does not swell on its surface even when a solvent-type ink is attached thereto, and therefore can be suitably used as a paper transport belt in an inkjet system. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Base material layer] The base layer of the present invention must be made of a composition containing a polyethylene resin, a polyamide resin, and a conductive agent. If necessary, other resins may be added to the composition within a range that does not impair the properties of the base layer.

[0012] The polyethylene resin used in the present invention is a polymer made of ethylene, and includes copolymers having polyethylene as a partial structure. Examples of polyethylene resins include high density polyethylene (density: 0.942 to 0.96), medium density polyethylene (density: 0.93 to 0.942), low density polyethylene (density: 0.91 to 0.93), very low density polyethylene (density: less than 0.91), linear low density polyethylene, etc., and an example of a copolymer having polyethylene as a partial structure is ethylene-vinyl acetate copolymer (called EVA), which is a copolymer of ethylene and vinyl acetate, etc.

[0013] In addition, a conductive belt for an image forming apparatus, which is one of the applications of the conductive belt of the present invention, is used by being stretched between rolls with a certain tension, but since the conductive belt is left stretched between rolls when a printer or the like is stopped, it becomes bent. This causes a problem that the bent part becomes convex when the printer or the like is started. If a film made of a thermoplastic resin is left in the same shape for a long time, it is inevitable that the bent part will become convex, but a conductive belt with a low tensile modulus of elasticity is stretched between rolls and tension is applied when a printer or the like is started, and the convex part of the bent part is alleviated. For this reason, it is preferable that the tensile modulus of elasticity of the polyethylene resin is 1100 MPa or less. In addition, in recent years, with the increasing speed of printers, etc., if the tensile modulus of the conductive belt for image forming apparatus falls below 400 MPa, the belt will stretch during driving, which is not preferable. As described above, there are various types of polyethylene resins, and low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene have a tensile modulus of about 200 to 300 MPa, so that the tensile modulus can be adjusted by using high-density polyethylene in combination with low-density polyethylene, linear low-density polyethylene, very low-density polyethylene, etc. according to the application.

[0014] Polyamide resins are thermoplastic resins with sufficient molecular weight obtained by polycondensation of diamines and dicarboxylic acids, polycondensation of α,ω-aminocarboxylic acids, ring-opening polymerization of lactams, etc. Examples of polyamide resins include nylon 6, nylon 4, nylon 6,6, nylon 11, nylon 12, nylon 6,10, nylon 6,12, nylon 6 / 6,6, nylon 6 / 6,6 / 12, nylon 6,MXD (MXD represents m-xylylenediamine component), nylon 6,6T (T represents terephthalic acid component), nylon 6,6I (I represents isophthalic acid component), etc. Among these, polyamide resins with low water absorption are preferred, and polyamide resins with low water absorption are excellent in dispersibility of carbon black and excellent in stability of electrical resistance in high humidity environments. The water absorption of polyamide resins is preferably 1.5% or less, more preferably 1.0% or less. Examples of polyamide resins having a water absorption rate of 1.5% or less include nylon 11, nylon 12, nylon 6,10, and nylon 6,12, and examples of polyamide resins having a water absorption rate of 1.0% or less include nylon 11 and nylon 12. These polyamides may be used alone or in combination of two or more kinds.

[0015] In order to uniformly disperse the polyamide resin in the polyethylene resin, a compatibilizer may be added to the composition forming the base layer of the present invention. The compatibilizer is preferably a modified polyethylene resin containing an epoxy group, a carboxyl group, or an anhydride group. By using a modified polyethylene having an epoxy group, a carboxyl group, or an anhydride group that is reactive with the amino group that is the terminal group of the polyamide resin as the compatibilizer, a sea-island structure in which the polyamide resin is finely dispersed in the polyethylene resin matrix is ​​formed. Carbon black and ion-conductive materials, which are conductive agents, are unevenly distributed in the polyamide resin to which they have a higher affinity, and as a result, the conductive agent can be uniformly dispersed in the polyethylene resin matrix.

[0016] Examples of the compatibilizer include terpolymers of ethylene-methyl acrylate-maleic anhydride, terpolymers of ethylene-ethyl acrylate-maleic anhydride, terpolymers of ethylene-butyl acrylate-maleic anhydride, copolymers of ethylene-glycidyl methacrylate, and terpolymers of ethylene-methyl acrylate-glycidyl methacrylate, and may contain structural units derived from other monomers. Examples of the other monomers include α-olefins such as propylene and butene, styrene, vinyl acetate, (meth)acrylate, and (meth)acrylonitrile. The other monomers may be used alone or in combination of two or more. The content of the other monomers is 0 to 15 mol%, preferably 0 to 10 mol%, and more preferably 0 to 5 mol%. The number average molecular weight of the compatibilizer is preferably 3000 or more. If the number average molecular weight of the compatibilizer is less than 3000, the unreacted compatibilizer may bleed out to the surface of the base layer (bleed phenomenon). This bleeding phenomenon can cause contamination of paper and other parts in a conductive belt for an image forming apparatus.

[0017] The tensile modulus of the base layer is preferably 500 MPa or more, more preferably 700 MPa or more. In order to increase the tensile modulus of the belt, the content of high density polyethylene in the above-mentioned polyethylene resin can be increased, or a reinforcing material such as a plate-like filler or whiskers can be added. The thickness of the base layer is preferably 30 to 300 μm, more preferably 40 to 200 μm, so as to satisfy the above performance. If the thickness is less than 30 μm, it is difficult to obtain a stable electrostatic adsorption force of the belt, and if the thickness exceeds 300 μm, the flexibility is deteriorated.

[0018] In the conductive belt of the present invention, the surface resistivity of the base layer can be adjusted by blending a conductive agent in the base layer. 5 ~1×10 12 Ω / □, and particularly in the medium resistance region of 1×10 5 ~1×10 8The conductive agent may be an electronic conductive material or an ion conductive material. In addition, the substrate layer may be in a lower resistance region (for example, 1×10 5 ~1×10 6 When a high resistance (Ω / □) is required, it is preferable to use an electronically conductive material that can reduce electrical resistance with a small amount of addition.

[0019] Examples of the electronic conductive material include carbon-based materials such as carbon black, graphite, and carbon nanotubes; conductive polymers such as polyaniline, polythiophene, and polyacetylene; and conductive inorganic particles such as inorganic particles surface-treated with aluminum-zinc oxide, antimony-tin oxide, indium-tin oxide, and carbon black. Examples of carbon black include conductive carbon black such as furnace black, channel black, ketjen black, and acetylene black. In particular, carbon black with an average particle size of 50 nm or less is preferred because it can reduce electrical resistance with a small amount of carbon black. In addition, from the viewpoint of developing the structure of the carbon black and forming a conductive path, the DBP (Dibutyl Phthalate) oil absorption is preferably 100 to 500 ml / 100 g, more preferably 100 to 300 ml / 100 g, and more preferably 150 to 250 ml / 100 g. In addition, from the viewpoint of electrical conductivity, the DBP (Dibutyl Phthalate) oil absorption is preferably 30 to 1500 m 2 Carbon black having a BET surface area in the range of 1 / g is preferred. In the present invention, grafted carbon black to which a polymer having one or more functional groups selected from a carboxyl group, a hydroxyl group, an epoxy group, an amino group, and an oxazoline group is grafted, or carbon black surface-treated with a low molecular weight compound may also be used.

[0020] The amount of the electronic conductive material is preferably 5 to 25 parts by weight, and more preferably 8 to 20 parts by weight, per 100 parts by weight of the total amount of the polyethylene resin and the polyamide resin. If the amount of the conductive agent is less than 5 parts by weight, it may not be possible to obtain a composition exhibiting the desired semiconductivity, whereas if it exceeds 25 parts by weight, the melt viscosity increases, making melt extrusion difficult.

[0021] Examples of ion-conductive materials include polyetheresteramide, polyetherester, polyetheramide, polyethylene oxide, polyethylene oxide copolymer, partially cross-linked polyethylene oxide copolymer, ionic electrolytes, etc., which can be used alone or in combination of two or more. As the ionic electrolyte, alkali metal thiocyanate, phosphate, sulfate, halogen-containing oxyacid salt, and tetraalkylammonium salt can be used alone or in combination of two or more. Among these, lithium perchlorate, sodium perchlorate, potassium perchlorate, lithium thiocyanate, sodium thiocyanate, and potassium thiocyanate are preferred.

[0022] When an ion conductive material is used as the conductive agent, the amount of the conductive agent is preferably 1 to 50 parts by weight per 100 parts by weight of the total amount of the polyethylene resin and the polyamide resin. The amount is preferably 1 to 30 parts by weight, more preferably 2 to 25 parts by weight, and more preferably 15 to 25 parts by weight. If the amount of the ion conductive material is less than 1 part by weight, it is not preferable because a composition exhibiting a predetermined conductivity cannot be obtained, and if it exceeds 50 parts by weight, it is not preferable because the hygroscopicity increases and the tensile modulus decreases.

[0023] The resin composition used in the base layer of the present invention may contain additives as necessary within the range that does not impair its properties. Examples of additives include antioxidants, heat stabilizers, organic fillers, inorganic fillers, antiblocking agents, plasticizers, lubricants, processing aids, etc. These resins and additives can be used in appropriate amounts depending on the purpose.

[0024] The composition ratio of each component of the composition forming the base layer of the present invention is not particularly limited, but it is preferable that the polyethylene resin and the polyamide resin are contained in a ratio of polyethylene resin:polyamide resin=70% by weight to 92% by weight:30% by weight to 8% by weight. The ratio of the polyamide resin in the total amount of the polyethylene resin and the polyamide resin, 100% by weight, is more preferably 10% by weight to 25% by weight, and further preferably 12% by weight to 20% by weight. By setting the blending ratio of the polyethylene resin and the polyamide resin in the above range, a sea-island structure in which the polyamide resin is finely dispersed in the polyethylene resin matrix is ​​obtained, and thus the conductive agent is uniformly dispersed, thereby exhibiting excellent uniformity of electrical resistance. If the polyamide resin is less than 8% by weight, the interval between the islands in the sea-island structure becomes large, and the uniformity of the electrical resistance may be deteriorated.

[0025] The amount of the compatibilizer is preferably 0.3 to 5.0 parts by weight, more preferably 0.5 to 2.0 parts by weight, based on 100 parts by weight of the total amount of the polyethylene resin and the polyamide resin. By setting the amount of the compatibilizer in the above range, a sea-island structure in which the polyamide resin is finely dispersed in the polyethylene resin matrix is ​​obtained, and the conductive agent is uniformly dispersed in the composition, thereby exhibiting excellent uniformity of electrical resistance. If the amount of the compatibilizer is less than 0.3 parts by weight, the size of the islands in the sea-island structure becomes large, making it difficult to obtain stable electrical resistance in the medium resistance range, and the breaking elongation of the film may decrease. On the other hand, if the amount of the compatibilizer is more than 5 parts by weight, the size of the islands in the sea-island structure may become too small, and the amount of the conductive agent required to obtain electrical resistance in the medium resistance range increases, which is undesirable because the electrical resistance in the TD direction varies greatly when the film is formed into a belt shape. For these reasons, the size of the islands in the sea-island structure in the composition forming the base layer is preferably 0.5 to 5.0 μm, and more preferably 0.8 to 3.0 μm.

[0026] [Adhesive layer] The adhesive layer of the present invention is essential to be made of a composition containing an epoxy group-containing polyethylene resin. The composition may be made of only an epoxy group-containing polyethylene resin, or may contain other resins or additives as necessary within the range that does not impair the properties. When a conductive belt consisting of a base layer containing a polyethylene resin, a polyamide resin, and a conductive material and a surface layer containing an acid-modified ethylene-tetrafluoroethylene resin is produced by a co-extrusion method, the interlayer adhesive strength is weak and the belt is easily peeled off. The adhesive layer of the present invention is a layer necessary for bonding the base layer and the surface layer, and the presence of the adhesive layer allows the functional groups of the surface layer, such as carboxyl groups, to react with the epoxy groups of the adhesive layer, thereby firmly bonding the surface layer and the adhesive layer. Examples of epoxy group-containing polyethylene resins include copolymers of ethylene-glycidyl methacrylate, ternary copolymers of ethylene-glycidyl methacrylate-ethyl acrylate, and ternary copolymers of ethylene-glycidyl methacrylate-vinyl acetate.

[0027] The thickness of the adhesive layer is preferably 2 to 80 μm, more preferably 5 to 50 μm, so as to satisfy the above performance. In the co-extrusion method, if the thickness of the specific layer (adhesive layer) is less than 2 μm, there is a risk of generating areas where the specific layer is not present, and if the thickness of the adhesive layer exceeds 80 μm, the thickness of the insulating layer (the total thickness of the adhesive layer and the surface layer) becomes thick, and the electrostatic adsorption force decreases.

[0028] [Surface layer] The surface layer of the present invention is essentially made of a composition containing an acid-modified ethylene-tetrafluoroethylene copolymer. The composition may consist of only an acid-modified ethylene-tetrafluoroethylene copolymer, or may contain other resins and additives as necessary within a range that does not impair the properties of the composition. The acid-modified ethylene-tetrafluoroethylene copolymer is a copolymer that contains at least a polymerization unit based on ethylene, a polymerization unit based on tetrafluoroethylene, and a polymerization unit having an acid structure. Examples of the polymerized units having an acid structure include unsaturated carboxylic anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, etc., and unsaturated carboxylic acids such as undecylenic acid, acrylic acid, methacrylic acid, maleic acid, etc. The content of the polymerized units having an acid structure is preferably 0.01 to 10 mol %, more preferably 0.1 to 5 mol %, based on the total polymerized units in the acid-modified ethylene-tetrafluoroethylene copolymer.

[0029] A surface layer made of a composition containing an acid-modified ethylene-tetrafluoroethylene copolymer and a base layer made of a composition containing a polyethylene resin, a polyamide resin, and a conductive agent have poor adhesion even when extruded as two layers by a co-extrusion method. However, by providing an adhesive layer made of a composition containing an epoxy group-containing polyethylene resin, the interlayer adhesive strength between the surface layer and the base layer is increased. The surface resistivity of the surface layer of the conductive belt of the present invention is 1×10 13 Ω / □ or more is preferable, 1×10 14 More preferably, the surface resistivity is 1×10 Ω / □ or more. Among fluororesins, ethylene-tetrafluoroethylene copolymers and acid-modified ethylene-tetrafluoroethylene copolymers in particular have a surface resistivity of 1×10 14 It is preferable because it has excellent insulation properties, being Ω / □ or more. Furthermore, it has been found that the surface layer used in the present invention does not swell even if solvent ink adheres to the surface of the conductive belt, because it uses a fluorine-based resin.

[0030] [Method of manufacturing a belt for an image forming apparatus] The method for producing the composition for forming the base layer of the present invention is not particularly limited, and examples thereof include a method in which a polyethylene-based resin, a polyamide-based resin, a conductive agent, and additives used as necessary are mixed and dry blended, and then melt-kneaded; a method in which a polyethylene-based resin and a conductive agent are melt-kneaded in advance to prepare a master batch, and then a polyamide-based resin and additives used as necessary are melt-kneaded into the master batch.

[0031] Apparatuses for melt-kneading include various known kneading machines such as a batch kneader, a kneader, a co-kneader, a Banbury mixer, a roll mill, a single-screw or twin-screw extruder, etc. Among these, a single-screw extruder or twin-screw extruder is preferably used because of its excellent kneading ability and productivity.

[0032] The temperature during melt kneading can be appropriately selected depending on the type and melt viscosity of the polyethylene resin or polyamide resin used, but is usually in the range of 150 to 300°C, and preferably 170 to 280°C from the viewpoint of preventing deterioration of the resin.

[0033] The conductive belt of the present invention can be manufactured by extrusion molding, centrifugal molding, dipping, and the like. The extrusion molding, particularly the extrusion molding using an annular die, is preferable because it can obtain a seamless belt. As the extrusion molding using an annular die, for example, an extrusion molding device can be used in which three extruders are arranged below the extruders, an annular die communicating with the extruders is arranged below the annular die, and a mandrel is arranged below the annular die to support the molten resin extruded downward from the annular die on its outer periphery and cool and solidify it. A tubular molded body can be obtained by supplying a composition forming a base layer, a resin forming an adhesive layer, and a resin forming a surface layer to each extruder, co-extruding them from one annular die into a tubular shape, and cooling and solidifying them along the outer periphery of the mandrel. Then, the obtained tubular molded body can be cut to a desired width to make a belt. Note that these explanations were for three layers, but when there are four or more layers, it is sufficient to prepare an extruder and a die according to the number of layers.

[0034] The conductive belt of the present invention can be suitably used as a part for an image forming apparatus such as an intermediate transfer belt, a transfer conveyor belt, a paper conveyor belt, etc. In particular, the conductive belt of the present invention can be suitably used as a paper conveyor belt for an inkjet system using a solvent ink, since the belt surface does not swell even if a solvent ink adheres to the belt surface. EXAMPLES

[0035] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. The physical properties in the examples were measured as follows. (1) Melt Viscosity The melt viscosity was measured using a Shimadzu Koka type flow tester equipped with a die having a hole of 10 mm length x 1 mm diameter. (2)Surface resistivity The surface resistivity was measured using a Hiresta UX (MCP-HT800, manufactured by Dia Instruments) equipped with a URS probe (load 2 kg) (applied voltage of 10 V for the substrate layer and 1000 V for the surface layer). The uniformity (variation) of the surface resistivity was calculated using the following formula. Uniformity of surface resistivity [digits] = log10 (maximum surface resistivity / minimum surface resistivity) (3) Interlayer adhesion between the base layer and the surface layer In the belts obtained in each of the Examples and Comparative Examples, it was confirmed whether the base layer and the surface layer were adhered to each other, and the adhesion was evaluated based on the following evaluation criteria. ◯: The base layer and the surface layer are firmly bonded together (through the adhesive layer). ×: The base layer and the surface layer are adhered to each other but can be peeled off by hand, or the layers are easily peeled off from each other. (4) Solvent-resistant ink Solvent ink (a high-boiling petroleum-based solvent with a boiling point of 100°C or higher) was dropped onto the surface layer of the belt obtained in each Example and Comparative Example, and the belt was left at 60°C for 24 hours. The solvent ink was then wiped off, and the surface was observed and evaluated based on the following evaluation criteria. ◯: The film surface did not swell or deform. Δ: The film surface was slightly swollen and slightly deformed. ×: The film surface swelled and was obviously deformed. (5) Warping of the belt end The belts obtained in each of the Examples and Comparative Examples were left to stand for one day under high temperature and high humidity conditions (30° C.×70% RH), and then the warping of the belt ends was observed and evaluated based on the following evaluation criteria. ○: No warping occurred at the belt end. ×: The belt end is warped toward the surface layer.

[0036] The following raw materials were used: <Thermoplastic resin (A)> High density polyethylene resin (A-1) [Melting point: 132°C, Melt viscosity: 9240 poise (measurement temperature 200°C, load 100 kg] Low-density polyethylene resin (A-2) [Melting point: 111°C, melt viscosity: 2300 poise (measurement temperature 200°C, load 100 kg] Polyamide resin (A-3) [Melting point: 178°C, Melt viscosity: 5000 poise (measurement temperature: 200°C, load: 100 kg] Compatibilizer (A-4) [Ethylene-ethyl acrylate-maleic anhydride terpolymer (mixture ratio: ethylene:ethyl acrylate:maleic anhydride = 92:5:3, melting point: 107°C, melt viscosity: 830 poise (measurement temperature 200°C, load 100 kg)] Acid-modified ethylene-tetrafluoroethylene copolymer (A-5) [Melting point: 190°C, melt viscosity: 6750 poise (measurement temperature: 220°C, load: 100 kg)] Polyvinylidene fluoride (A-6) [Melting point: 168°C, melt viscosity: 4500 poise (measurement temperature: 200°C, load: 100 kg)] Ethylene-glycidyl methacrylate copolymer (A-7) (mixture ratio: ethylene:glycidyl methacrylate = 88:12) Ethylene-glycidyl methacrylate copolymer (A-8) (mixture ratio: ethylene:glycidyl methacrylate = 92:8) <Conductive agent (B)> Carbon black (B-1) [DBP oil absorption: 190ml / 100g, BET surface area: 70m2 / g]

[0037] [Base material layer] The polyethylene-based resin, polyamide-based resin, conductive agent, and compatibilizer were melt-kneaded using a twin-screw kneading extruder with a screw diameter of 38 Φmm so as to obtain the resin compositions for the base layer of Examples 1 and 2 and Comparative Examples 1 to 6, in the compounding ratios shown in Table 1.

[0038] [Examples and Comparative Examples] Using an apparatus equipped with three extruders with a cylinder diameter of 50 mm and three-layer annular dies attached to the tips, the resin composition for forming the base layer shown in Table 1 was supplied to the extruder for the inner layer, the resin for the adhesive layer was supplied to the extruder for the intermediate layer, and the resin for forming the surface layer was supplied to the extruder for the surface layer. They were then molded into a tubular shape by co-extrusion and cut to a length of 350 mm to obtain a seamless belt with a circumference of 800 mm and a width of 350 mm, with the base layer as the inner layer and the surface layer as the outer layer. The evaluation results of the conductive belts produced in the examples and comparative examples are shown in Table 1.

[0039] [Table 1]

[0040] As shown in Table 1, in Examples 1 and 2, which are conductive belts having a base layer made of a resin composition containing a polyethylene resin, a polyamide resin, and a conductive agent, an adhesive layer made of an epoxy group-containing polyethylene resin, and a surface layer made of an acid-modified ethylene-tetrafluoroethylene copolymer, the surface resistivity on the base layer side is 1×10 6 ~1×10 7 The surface resistivity of the substrate layer was excellent (less than one digit). The surface resistivity of the surface layer was also excellent (less than one digit). 14 The value was Ω / □ or more, and the insulation was excellent. In addition, the interlayer adhesion was good, the surface layer had good resistance to solvent ink, and the belt edge did not warp even when left under high temperature and high humidity. In contrast, Comparative Example 1, which is a two-layer conductive belt having a base layer made of a resin composition containing a polyethylene resin, a polyamide resin, and a conductive agent and a surface layer made of an acid-modified ethylene-tetrafluoroethylene copolymer, had poor adhesion between the base layer and the surface layer, and the layers easily peeled off. Comparative Example 2, which is a two-layer conductive belt composed of a base layer made of a polyamide resin and a conductive agent and a surface layer made of an acid-modified ethylene-tetrafluoroethylene copolymer, had a polyamide resin base layer, so the belt end warped and was unsuitable as a belt.

[0041] Comparative Examples 3 and 4, in which a polyamide-based resin or a polyethylene-based resin was used as the surface layer, had excellent uniformity in the surface resistivity of the base layer, but when solvent ink was dropped onto the surface layer and left at 60°C for 24 hours, swelling was observed, and the belt was particularly unsuitable as a paper transport belt for an inkjet system using solvent ink. On the other hand, Comparative Example 5, in which a polyvinylidene fluoride surface layer was used, had good solvent ink resistance for the surface layer, but poor adhesion to the base layer made of a resin composition containing a polyethylene-based resin, a polyamide-based resin, and a conductive agent, and peeling occurred easily between the layers, and the surface resistivity of the surface layer side was also 1×10 13 ~1×10 14 The insulation resistance was in the range of Ω / □ and was poor. In addition, Comparative Example 6, which is a conductive belt including a base layer made of a resin composition containing a polyethylene resin, a polyamide resin, and a conductive agent, an adhesive layer made of a polyamide resin, and a surface layer made of an acid-modified ethylene-tetrafluoroethylene copolymer, showed adhesion to the acid-modified ethylene-tetrafluoroethylene copolymer and had poor interlayer adhesion, even though the polyamide resin A-3 contained in the base layer was used as the adhesive layer.

Claims

1. A conductive belt comprising: a substrate layer made of a composition containing a polyethylene resin, a polyamide resin, and a conductive agent; an adhesive layer made of a composition containing an epoxy group-containing polyethylene resin; and a surface layer made of a composition containing an acid-modified ethylene-tetrafluoroethylene copolymer.

2. 2. The conductive belt according to claim 1, wherein the composition for forming the base layer further contains a compatibilizer.

3. 3. The conductive belt according to claim 1, wherein the epoxy group-containing polyethylene resin is an ethylene-glycidyl methacrylate copolymer.

4. 4. The conductive belt according to claim 1, wherein the conductive agent is an electron conductive material.

5. 5. The conductive belt according to claim 4, wherein said electron conductive material is carbon black.

6. The surface resistivity of the substrate layer side at a temperature of 23° C. and a relative humidity of 50% RH is 1×10 5 Ω / □ or more 1×10 8 6. The conductive belt according to claim 1, wherein the resistance is Ω / □ or less.

7. The surface resistivity of the surface layer side at a temperature of 23° C. and a relative humidity of 50% RH is 1×10 13 7. The conductive belt according to claim 1, wherein the resistance is Ω / □ or more.

8. 8. The conductive belt according to claim 1, which is used in an image forming apparatus.

9. 9. The conductive belt according to claim 1, which is used in an ink-jet type image forming apparatus.

10. 10. An image forming apparatus comprising the conductive belt according to claim 1.

11. 10. A method for producing a conductive belt according to claim 1, wherein a composition for forming a base layer containing a polyethylene resin, a polyamide resin and a conductive agent, a composition for forming an adhesive layer containing an epoxy group-containing polyethylene resin, and a composition for forming a surface layer containing an acid-modified ethylene-tetrafluoroethylene copolymer are each supplied to separate extruders, and are co-extruded from a circular die so that the base layer is the inner layer, the adhesive layer is the intermediate layer, and the surface layer is the outer layer.

Citation Information

Patent Citations

  • Production of intermediate transfer body and image forming device

    JP2000235313A

  • Polyamide-based electronic photographic material

    JP2004210828A

  • Electrophotographic endless belt, method for producing electrophotographic endless belt, and electrophotographic apparatus

    JP2006119608A

  • Transfer belt for ink jet and ink jet recording apparatus

    JP2008094605A

  • Fuel tube

    JP2008100503A